VIEWS OF NEW ENLIGHTENMENTALISTS ON FORMING FAMILY RELATIONSHIPS IN YOUNG PEOPLE. (Universal International Scientific Journal, 2026)
This article reveals the ideas and goals of the Jadids in creating healthy family relationships among young people. It also reflects the ideas of figures such as Abdulla Avloni, Abdurauf Fitrat, and Haji Muin about how boys and girls should be educated.
Keywords: society, family, new generations, child upbringing, boys and girls, Abdurauf Fitrat's thoughts, future generation, parents